The use of Picture in Increasing Students’ Vocabulary Mastery on Writing Skill: An Action Research at The First Grade Students of SMPN 1 Kayangan In Academic Yeacr 2022/2023 - Wahab, Abdul; Syahrul Hafiz, Haerori (PENA : Jurnal Pendidikan Bahasa, Sastra, & Pengajaran, 2022)
This research is the use of pictures in increasing students’ vocabulary mastery at the first Grade Students of SMP Negeri 1 Kayangan in Academic Year 2022/2023. The kind of this research is a classroom action research (CAR). The populations of this research were all students of the first grade student of SMPN 1 Kayangan that consists of 117 students. Meanwhile the subject research was VII c because they were less in mastery vocabulary, then the technique of collecting data was observation and test. In addition in analyzing the numerical data, the researcher gained the average students score in each cycle, the mean score of the first cycle was 5.73 and at the second cycle was 7.48, and the curriculum standar of Minimum Completness Criteria (MCC) at the first cycle was 53.57% it had not reached yet the classical sucsessful criteria, because the classical successful learning must be >60% and at the second cycle was 71.42%, so it can be said succes because 71.42% higher than >60. It can be concluded that the use of picture was able to increase the students’ vocabulary mastery at the first grade students of SMPN 1 Kayangan in academic year 2022/2023.